2021
DOI: 10.12669/pjms.37.3.3848
|View full text |Cite
|
Sign up to set email alerts
|

Is leukopenia and lymphopenia a characteristic feature of COVID-19 in children?

Abstract: Objectives: To analyze whether leucopenia and lymphopenia a characteristic feature of children with COVID-19 and to find out its association with the disease severity. Methods: This was a descriptive cross-sectional study conducted at The Children’s Hospital Lahore from March 2020 to October 2020. All confirmed cases of COVID-19 infection and post-COVID MIS-C/Kawasaki Disease diagnosed on the basis of RT-PCR and Antibody test respectively were included. Complete blood and differential counts were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
4
20
1
Order By: Relevance
“…We identified 9937 potentially relevant records from the literature databases and registers, and 1575 records from the additional searches. After screening the titles, abstracts and full texts, 56 studies (22 cohort studies, 9 case-control studies, and 25 case series) with a total of 79,104 patients were included [ [10] , [11] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 9937 potentially relevant records from the literature databases and registers, and 1575 records from the additional searches. After screening the titles, abstracts and full texts, 56 studies (22 cohort studies, 9 case-control studies, and 25 case series) with a total of 79,104 patients were included [ [10] , [11] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 studies assessed risk factors for progression to severe or critical disease [ 25 , 26 , 28 , 30 , 33 , 36 , 42 , 49 , [51] , [52] , [53] , 55 , 59 , 60 , 61 , 63 , [65] , [66] , [67] , [68] , [69] , 71 , 76 ]. Neurological diseases ( OR =5.16, 95% CI 2.30 to 11.60, five studies, moderate-quality evidence) increased the odds of severe or critical disease.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had shown that COVID-19-infected adult exhibited reduced lymphocyte and elevated platelet counts although there was no decrement in children. 1 - 3 These observations suggested that platelet-to-lymphocyte ratio (PLR) might be a new indicator in the monitoring of patients with COVID-19. 2 , 4 , 5 Clinical research of 456 patients with COVID-19 showed that severe cases had higher neutrophil-to-lymphocyte ratio (NLR) and lower lymphocyte count than less severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 27, 2022. ; https://doi.org/10.1101/2022.06. 23.22276825 doi: medRxiv preprint complications in children as well. Furthermore, children may not have symptoms even during the acute disease.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%